2022
DOI: 10.3390/molecules27072056
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Leptulipin, a New Anticancer Protein from theIranian Scorpion, Hemiscorpius lepturus

Abstract: Cancer is one of the leading causes of mortality in the world. Unfortunately, the present anticancer chemotherapeutics display high cytotoxicity. Accordingly, the discovery of new anticancer agents with lower side effects is highly necessitated. This study aimed to discover an anticancer compound from Hemiscorpius lepturus scorpion venom. Bioactivity-guided chromatography was performed to isolate an active compound against colon and breast cancer cell lines. 2D electrophoresis and MALDI-TOF were performed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The detected PLA 2 has encoded a protein of 144 amino acid residue named Maurolipin. Till now, several studies reported the genes encoding phospholipases A 2 from different species of scorpions, including Hemilipin from H. lepturus [ 23 ], Leptulipin from H. lepturus [ 25 ], Imperatoxin I and Phospholipin from P. imperator [ 21 , 22 ], Phaiodactylipin from A. phaiodactylus [ 20 ], Heteromtoxin from Heterometrus laoticus [ 10 ], Phospholipase A 2 from H. fulvipes [ 46 ], MtPL A 2 from Mesobuthus tumulus [ 47 ], Sm-PLVG from Tunisian S. maurus [ 27 ], and Phospholipase A 2 from Hadrurus gertschi [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detected PLA 2 has encoded a protein of 144 amino acid residue named Maurolipin. Till now, several studies reported the genes encoding phospholipases A 2 from different species of scorpions, including Hemilipin from H. lepturus [ 23 ], Leptulipin from H. lepturus [ 25 ], Imperatoxin I and Phospholipin from P. imperator [ 21 , 22 ], Phaiodactylipin from A. phaiodactylus [ 20 ], Heteromtoxin from Heterometrus laoticus [ 10 ], Phospholipase A 2 from H. fulvipes [ 46 ], MtPL A 2 from Mesobuthus tumulus [ 47 ], Sm-PLVG from Tunisian S. maurus [ 27 ], and Phospholipase A 2 from Hadrurus gertschi [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…sPLA 2 from the venom glands of scorpions is classified as a group III subfamily [20]. sPLA 2 has been identified from different species of scorpions till now, including Pandinus imperator [21,22], Hemiscorpius lepturus [23][24][25], Anuroctonus phaiodactylus [20], Heterometrus fulvipes [26], Heterometrus laoticus [10], and Tunisian Scorpio maurus [27].…”
Section: Introductionmentioning
confidence: 99%
“…The final isolated fraction with distinctive cytotoxic activity was then identified by 2-DGE. The bioactivities of Hemiscorpius lepturus peptides discovered in specific fractions constitute novel biomolecules with potential pharmacological use [ 84 ]. Different neurotoxins in scorpion venom are accountable for the various envenomation effects in humans, especially cardiotoxic peptides that cause severe cardiorespiratory complications to envenomation victims [ 85 ].…”
Section: Implementation Of Separation Methods For Scorpion Venomsmentioning
confidence: 99%